The content of Recovery College courses in England: a 71 college document analysis - Takhi, Simran Kaur; Brown, Holly Hunter; Ronaldson, Amy; Lawrence, Vanessa; McPhilbin, Merly; Ingall, Benjamin Rose; Daryanani, Riddhi; Simpson, Jonathan; Jebara, Tesnime; Lawrence, Simon; Kapka, Agnieszka; Kotera, Yasuhiro; et al. (Frontiers in Psychiatry, 2025)
IntroductionRecovery Colleges (RCs) exist in 28 countries and across five continents. The concept of recovery and recovery-oriented care has become widespread internationally and embedded in policy documentation and mental health services. As a result, Recovery Colleges, which focus on adult learning and co-production, have now developed a global presence, but many psychiatrists are unfamiliar with this intervention. RCs can be categorized as ‘Strengths Oriented’, focusing on skills and knowledge development, or ‘Community-oriented’, emphasizing strengthening community and social connections. Research has not sufficiently investigated RC curriculum and how course provision differs depending on RC orientation. The study aimed to develop a typology of RC courses and assess differences in course types across RC orientations.MethodA document analysis was conducted. The websites of 88 RCs in England were searched to collect online prospectuses. Overall, 2,330 courses described in 551 documents from 71 RCs were collated. Inductive content analysis was applied to the course titles to develop a typology of courses offered. Mann-Whitney U tests were used to assess differences in the median number of course types offered by Strengths-Oriented versus Community-Oriented colleges.ResultsA typology of 14 superordinate course categories was created. The three most common course categories were Self-management of Well-being (96% RCs ≥1 course, median 10 courses per RC), Mental Health Conditions and Symptoms (85% RCs ≥1 course, 4 courses per RC), and Creativity (86% RCs ≥1 course, 3 courses per RC). The least common course categories included Issues relating to the Extended Support Network and Issues relating to Staff (38% RCs ≥1 course, 0 courses per RC) (6% RCs ≥1 course, 0 courses per RC). The median number of courses did not differ between Strengths-oriented versus Community-oriented RCs, with the exception of more Practical Life Skills (p=0.021) and Involvement, Co-production and Research (p=0.036) courses in Strengths-oriented RCs.ConclusionsRCs support mental health recovery through a diverse curriculum. Community-facing and strengths-based, health service-affiliated RCs offer similar courses. RCs prioritize equipping students with knowledge about living with mental health issues. Courses targeted to informal carers are lacking. Further cross-cultural extension of the typology is needed.